The Importance of Technological Innovation in Manufacturing Industry - Xie, Hongmei (International Journal of Management and Education in Human Development, 2023)
Manufacturing companies have fast product updates and fierce market competition. If the company's own technological innovation ability is weak, it is not conducive to the subsequent improvement of the company's competitiveness. In the complex and ever-changing international situation, simply introducing technology cannot solve the current problems of technological barriers and industrial bottlenecks, and even leads to being "choked". Only by valuing investment in scientific and technological innovation and enhancing independent scientific and technological innovation capabilities can we effectively improve the level of scientific and technological innovation and industrial competitive advantages. The value realized by enterprises can often be evaluated from the perspective of financial performance. Therefore, we can study the relationship between the research and innovation capabilities of the manufacturing industry and enterprise performance. This will help cultivate and form important strategic innovation forces in China's manufacturing industry. In the process of enterprise management, the relationship between technological innovation capability and financial performance is studied, and reasonable planning is made on how to carry out technological innovation activities, the time and amount of investment in technological innovation, in order to provide reference basis for enhancing one's own competitiveness. For investors, while evaluating a company's technological innovation capability, they should also pay attention to the regular changes brought about by technological innovation investment, and make correct judgments about the company's situation; For the government, understanding and studying the relationship between technological innovation capability and financial performance can provide policy support and assistance for IT enterprises' technological research and development, correctly guide IT enterprises to carry out technological research and development activities, and formulate relevant incentive policies, providing a reference basis for driving the development of the manufacturing industry.